The Influence of Recruitment, Competency, Performance Appraisal and Talent Management on Employee Performance with Job Satisfaction as an Intervening Variable in PT Kliring Berjangka Indonesia with Job Satisfaction as an Intervening Variable - Yanti, Ana Dwi; Indupurnahayu, Indupurnahayu; AMINDA, RENEA SHINTA (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study aims to analyze the influence of recruitment, competence, performance appraisal, and talent management on employee performance, with job satisfaction as an intervening variable in PT Kliring Berjangka Indonesia (KBI). The research method is used descriptive quantitative, using a questionnaire distributed directly to respondents, specifically the 61 employees of KBI and utilizing a Likert scale for measurement. The results show that recruitment, performance appraisal, and talent management have a positive and significant effect on employee performance. Recruitment also has a positive and significant effect on job satisfaction. However, competence does not show a significant impact on either employee performance or job satisfaction. This study highlights that improving recruitment processes, performance appraisals, and talent management can enhance employee performance, underscoring the importance of job satisfaction as a mediating variable. The findings provide practical implications for company management, emphasizing the need to focus on these areas to improve overall employee performance. Additionally, this study contributes to the literature by exploring the relationships between recruitment, competence, performance appraisal, talent management, job satisfaction, and employee performance within the context of financial services companies.